Tracking nutrition investments: Proposed nutrition budget tagging framework and typology for the national government agencies in the Philippines - Lyle Casas; Joy Bagas; Valerie Gilbert Ulep (Philippine Institute for Development Studies (PIDS), 2025)
This report proposes a framework in tagging nutrition expenditures of national government agencies. The framework was developed through exhaustive literature review and validation sessions with government agencies. It comprised of five levels (5) of classification elements namely: major intervention classification, program domain, program component classification, and specific interventions. Furthermore, it includes three (3) additional markers to group and tag nutrition-relevant line-item expenditures such as: risk factors of malnutrition, nutrition intervention focus area, and population demographic group. The national government could use the framework to assess the adequacy and efficiency of public spending on nutrition. Also, it could be used to determine the alignment of public spending with the Philippine Plan of Action for Nutrition (PPAN) and with reform actions such as Universal Healthcare (UHC) and multi-sectoral and life-course approaches to health and nutrition.
Keywords: 330; budget tagging; expenditure tracking; nutrition; Philippines